ACADEMIC BACKGROUND OF THE PROFESSIONS ELIGIBLE FOR VOCATIONAL TRAINING IN MEDICAL BIOCHEMISTRY IN THE REPUBLIC OF NORTH MACEDONIA - Bogdanska, Jasna; Tosheska Trajkovska, Katerina; Topuzovska, Sonja (Journal of Morphological Sciences; Vol 6 No 3 (2023): JMS, 2023)
Laboratory profession across Europe differs in academic background of the specialists in clinical chemistry. In our country, specialists in medical biochemistry/clinical chemistry hold basic education in general medicine (medical doctors MDs) or pharmacy (Masters of pharmacy). The length of the graduate studies in general medicine is six years with 360 ECTS, and the length for general pharmacy is five years with 300 European Credit Transfer and Accumulation System (ECTS). Few common subjects are studied during graduate studies for both profiles that differ in the ECTS, such as: Chemistry, Anatomy, Physiology, Biochemistry, Biophysics, Molecular and Cell Biology and Genetics, Microbiology, Pathophysiology, Pharmacology. The postgraduate training in medical biochemistry, as a monovalent specialization, for both profiles, ranges 4 years. Although the graduate syllabus in Masters of pharmacy doesnâ€™t have any clinical subject, the specialization program for both graduate profiles is the same, as well as the title. Presently, the total length of basic education for both profiles is 10.5 for MDs and 9.5 years respectively, and both profiles are registered in the European Register of Specialists in Laboratory Medicine. The main question arising for the perspective vocational training in medical biochemistry for medical doctors and pharmacists is: do we need different specialization programs for these profiles, bearing in mind different academic background and the need of our health care system?  Key words: Master of Pharmacy Syllabus, Integrated studies for medical doctor Syllabus, obligatory and elective subjects for graduate studies.